PrEP Familiarity, Interest, and Usage Among 364 Black and Hispanic Adults in Indiana - Campbell, Jessica T.; Adams, Olivia R.; Bennett-Brown, Margaret; Woodward, Brennan; Gesselman, Amanda N.; Carter, Gregory (Frontiers in Public Health, 2022)
Pre-exposure prophylaxis, or PrEP, is a once-daily preventative prescription pill against HIV for adults or adolescents who have sex or inject drugs. PrEP may be especially useful among Black and Hispanic Americans, who are particularly at risk for HIV in the United States. In spite of this vulnerability, rates of PrEP use in Black and Hispanic communities are low. Here, we examined familiarity with, prior usage of, and future interest in PrEP among 364 Black and Hispanic Indiana residents. Indiana is an important context for this work, due to severe HIV outbreaks in the area over the last 8 years. Around half of all participants had never heard of PrEP, with Hispanic participants being less familiar than Black participants. Prior PrEP use was low, at around 10%, and was lower for Hispanic than Black participants. Around 21% of all participants reported interest in PrEP after learning of it in our study. Further, participants identified strategies that would make discussions about PrEP with a medical provider more comfortable. Black and Hispanic participants reported feeling the most comfortable with addressing PrEP usage with providers if: (a) the provider was the one who brought up the subject of PrEP, (b) there was written information available to the patient (i.e., brochures), and (c) the patient already knew they qualified for the prescription in terms of personal eligibility and insurance coverage. Additional provider and patient education, as well as openness on the part of the provider, can help to lessen the disparities associated with PrEP need and actual PrEP usage.